Innovation Management and New Product Development - Trott, Paul (Pearson International Content, 2020)
Explore key concepts of managing innovation and engage with latest developments in the field   Innovation Management and New Product Development, 7th Edition, by Trott is an established textbook on innovation management, management of technology, new product development and entrepreneurship. It provides an evidence-based approach to managing innovation in a wide range of contexts, including manufacturing, services, small to large organisations and the private and public sectors. The book keeps you abreast of the recent developments in the field of innovation and how the subject is being discussed in the wider business world through up-to-date examples, case studies, illustrations and images in every chapter. Clear and informed coverage of the management processes of new product development, coupled with a practical orientation of taking you through real-life challenges and dilemmas, makes it an essential textbook for MBA, MSc and advanced undergraduate courses.   Pearson, the world’s learning company.